Head for business : Student's book and workbook - Naunton, Jon.; Nguyễn Văn Phước; Ban biên dịch First News. (Tp.HCM : Thống kê, 2002)
A common language; Work to live, live to work; Transitions.
Keywords: Anh ngữ; English language; Anh ngữ -- Thương mại; English language -- Business English